Storage Readiness Levels: communicating the maturity of site technical understanding, permitting and planning needed for storage operations using CO2. (September 2021) - Akhurst, Maxine; Kirk, Karen; Neele, Filip; Grimstad, Alv-Arne; Bentham, Michelle; Bergmo, Per
Highlights: Storage Readiness Levels framework communicates site appraisal achieved and activities remaining for operational CO2 storage Standardised framework based on experience of researchers, regulators and industry Framework is applied to 742 saline formation and hydrocarbon field sites and extends industry commercial development classification Framework enables comparison of levels of investment and duration of appraisal to achieve a permit-ready CO2 storage site. Abstract: A framework of Storage Readiness Levels (SRLs) is presented to communicate the entirety of technical appraisal, permitting and planning activities achieved at a potential CO2 storage site and what remains to be completed for CO2 storage operations. The schema, based on learning gained from the experience of researchers, regulators and industry from the 1990s, is described and assessed by application to 742 saline formation and hydrocarbon field sites, offshore the UK, Norway and The Netherlands. The framework is flexible to accommodate national differences in procedures and practise and the unique character of each site. It is applicable regardless of the time-scale of appraisal or scale of assessment. The framework is consistent with and extends the industry commercial project development classification to include categories for sites with a lesser level of data and evaluation. Application to the phases of appraisal of three sites illustrates that investigations may advance understanding by different pathways and rates. The standardised framework enables comparison of the experience of permitting and planning activities completed within different jurisdictions, the level of investment and the duration required to achieve permitted or permit-ready sites. It is intended that the framework of SRLs should be widely applied.